Operations management - Stevenson, William J. (McGraw-Hill/Irwin series operations and decision sciences, 2018)
Stevenson's Operations Management features integrated, up-to-date coverage of current topics and industry trends, while preserving the core concepts that have made the text the market leader in this course for over a decade. Stevenson's careful explanations and approachable format support students in understanding the important operations management concepts as well as applying tools and methods with an emphasis on problem solving. Through detailed examples and solved problems, short cases and readings on current issues facing businesses, and auto-gradable end of chapter problems and application-oriented assignments available in Connect Operations Management, students learn by doing, and the Thirteenth Edition continues to offer more support for 'doing Operations' than any other.